Highly efficient ethylene polymerisation by scandium alkyls supported by neutral fac-kappa3 coordinated N3 donor ligands. - Lawrence, S; Ward, B; Dubberley, SR; Kozak, C; Mountford, P (2003)
Reaction of [M(CH2SiMe3)3(THF)2] (M = Sc or Y) with the neutral fac-kappa3 N3 donor ligands (L) Me3[9]aneN3 or HC(Me2pz)3 gave the corresponding trialkyls [M(L)(CH2SiMe3)3]; activation of the scandium congeners with B(C6F5)3 in the presence of ethylene afforded highly active polymerisation catalysts (Me3[9]aneN3 = 1,4,7-trimethyltriazacyclononane).